(untitled) (Gaceta Técnica, 2020)
This paper refers to the design and calculation of a 30,00 m section of metal beam, for a proposed railway bridge in the city of El Vigía, capital of the Alberto Adriani Municipality of Mérida State, Venezuela. The location of the bridge corresponds approximately to a route proposed by the State Railway Institute, Maracaibo Lake Route, in the National Railway Plan. The calculation hypothesis was made using simply supported beams, however the CSI Bridge 2017 calculation tool was used. The design of the beam section was carried out using the AASHTO LRFD 2014 standard, the analysis considerations loads and combinations were based on AREMA 2004. The freight train was the AREMA COOPER E-80, which is the most common idealized locomotive in the analysis. Other designed elements were the concrete slab, elastomeric supports, diaphragms or separators and stiffeners. The design of a 30,00 m section of metal beam of section I of 1.70 m high was obtained with sheets of 5.00 cm thick at the core and 10,00 cm for each wing, with a width 80,00 cm, all in A36 steel. The slab placed was 30,00 cm thick and 250 kg/cm2 concrete.